Consumer Behavior in Digital Era : Bibliometric Analysis - Joval Ifghaniyafi Farras (International Journal of Management and Business Economics, 2025)
This study aims to map the evolution of scientific literature on consumer behaviour in the digital era through a bibliometric approach. Analyses were conducted using VOSviewer software to identify conceptual structures, keyword trends, and thematic clusters in the research. The visualisation results showed four main clusters: (1) consumer interaction and digital platforms, (2) consumer behaviour technology and analytics, (3) marketing strategies and customer engagement, and (4) consumption ethics and sustainability. Findings indicate that consumer behaviour is influenced multidimensionally by developments in digital technology, changing social values, and ethical awareness. This study emphasises the importance of integrating analytics technologies with human-centred approaches, algorithm transparency, and authentic brand narratives to build trust and sustainability. Future research is recommended to explore the intersection of digital technology and sustainability values, including the context of the metaverse, virtual reality and circular economy.